2021
DOI: 10.1037/tra0000971
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and mental health among first responders with different service roles.

Abstract: Objective: Studies suggest that physical activity (PA) improves psychological recovery in traumaexposed populations like first responders. However, trauma exposure varies among first responders in relation to their unique service roles and duties. The purpose of this study was to examine the interaction effect of service role (traditional vs. emotional support first responders) and PA on mental health outcomes. Method: Traditional (n ϭ 133) and emotional support (n ϭ 31) first responders completed assessments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
(92 reference statements)
1
8
0
Order By: Relevance
“…The fourth observational study (52) showed no relationship between physical activity and PTSD symptoms among a predominantly asymptomatic sample. This study was cross-sectional in design, whereas to the other three observational studies were longitudinal.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The fourth observational study (52) showed no relationship between physical activity and PTSD symptoms among a predominantly asymptomatic sample. This study was cross-sectional in design, whereas to the other three observational studies were longitudinal.…”
Section: Discussionmentioning
confidence: 95%
“…An observational study was conducted in 2021 to examine the interaction effect of service role (traditional vs emotional support first responders) and physical activity on mental health outcomes (52). In this study, traditional first responders were defined as police officers, firefighters, and paramedics, whereas emotional first responders were defined as those providing emotional support on scene, e.g., providing psychological support to family members immediately after a suicide.…”
Section: Observational Researchmentioning
confidence: 99%
“…It was found that first responders in North America have a higher PA level than first responders in Europe (Figure 4). The North American study included traditional and emotional support first responders (Meckes et al, 2020), and the European study examined fire fighters (Turner et al, 2018). The average MET values could be higher among North American first responders, since the study included police officers and Trauma Intervention Program volunteers (Meckes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The North American study included traditional and emotional support first responders (Meckes et al, 2020), and the European study examined fire fighters (Turner et al, 2018). The average MET values could be higher among North American first responders, since the study included police officers and Trauma Intervention Program volunteers (Meckes et al, 2020). Also, the European study included emergency control and administrative service workers, which may have similar PA to populations within office and administrative support (Turner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant measures analyzed for the present study are listed in the Measures section. For other studies published from this larger dataset (see McDonald et al, 2020; Meckes et al, 2021). Participants who completed the full battery of questionnaires were compensated with a $20 electronic gift card (Amazon or Visa).…”
Section: Methodsmentioning
confidence: 99%